Increased Periodontal Attachment Loss in Patients With Systemic Sclerosis. Issue 7 (1st July 2016) - Pischon, Nicole; Hoedke, Daniela; Kurth, Sven; Lee, Paul; Dommisch, Henrik; Steinbrecher, Astrid; Pischon, Tobias; Burmester, Gerd R.; Buttgereit, Frank; Detert, Jacqueline; Riemekasten, Gabriela
Abstract : Background: Patients with inflammatory rheumatic diseases and periodontitis share common pathogenetic characteristics, such as proinflammatory traits causative for tissue degradation and loss of function. The aim of the present case control study is to investigate the association between systemic sclerosis (SSc) and periodontitis. Methods: The association between SSc and periodontitis was examined in 58 SSc patients and 52 control patients, matched for age and sex. The periodontal examination included periodontal attachment loss (AL), probing depth, bleeding on probing, plaque index (PI), and gingival index (GI). Potential risk factors of periodontitis were assessed through patients' questionnaires. Results: In unadjusted analyses, patients with SSc had a significant 0.61 mm higher AL (95% confidence interval [CI] 0.24 to 0.97; P = 0.002) when compared with controls. In a stepwise logistic regression, including SSc status, age, sex, education, smoking, alcohol consumption, and body mass index, only SSc status, age, and sex remained significantly associated with periodontitis. Adjusted for age and sex, patients with SSc had a 0.52 mm higher AL compared with controls (95% CI 0.16 to 0.88; P = 0.005). The strength of the association of SSc with AL remained statistically significant after additional adjustment for PI (0.44 mm; 95% CI 0.02 to 0.86; P = 0.04) or GI (0.61 mm; 95% CI 0.24 to 0.97; P = 0.001). Conclusions: This study demonstrates higher AL in patients with SSc, which remained significant after adjustment. The study indicates a possible relationship between SSc and periodontitis.